Lucia Athanassaki and Frances B. Titchener (eds) Plutarch’s cities. - Müller , Christel (Journal of Greek Archaeology, 2024)
This book, a collective volume, is the fruit of a revisited conference held in Delphi in 2013 in honour of Anastasios Nikolaidis, Emeritus Professor of Classics at the University of Crete, who has taken a particular interest in Plutarch throughout his career. This book has all the qualities needed for use by amateurs and specialists alike: a common bibliography for all the articles and two detailed indices: “index locorum” on the one hand, “names and subjects” on the other. It brings together an international panel of excellent specialists, most of whom focus mostly on classical Greek philology and literature, with the exception of the historian Katerina Panagopoulou.